Analysis of the effects of the amplitude-phase errors on spatial spectrum and resolving performance of the MUSIC algorithm - WANG Ding; WANG Chao; WU Ying (Tongxin xuebao)
Based on the perturbation theorem of orthogonal projection matrix,the first-order statistical expression of spatial spectrum of the MUSIC algorithm was deduced and a quadratic equation for solving the mean signal-to-noise ra-tio（SNR） resolving threshold was derived,through which the corresponding SNR resolution threshold could be obtained. Compared to currently existing method,the first-order statistical expression of spatial spectrum only involves array manifold vector and source covariance matrix instead of the eigenvalue and eigenvector of the ideal array covariance matrix,besides,the mean SNR resolving threshold is suitable in the presence of power difference of two signal sources. Numerical experiments validate the correctness of theoretical analysis.